DIGITAL INHERITANCE AND ITCM: NECESSARY DELIMITATION OF THE CONCEPT AND ITS TAX IMPACTS (Reflection and Critique Law Magazine, 2024)
The purpose of this work was to verify the existence of a digital heritage and define its concept. This issue is gradually gaining importance, since the Internet and social networks make it possible to create a huge range of digital files with some ease, a circumstance that generates a state of permanence of the user on the network after his death. Through bibliographical research and analysis of legislation, it became possible to conclude favorably on the existence of digital heritage, with a well-defined concept, basically encompassing the issue of equity and intangible assets resulting from it. Consequently, the possibility of levying the Causa Mortis Transfer Tax was questioned, and a positive answer was found. Although the tax legislation is still silent on some topics, it contains all the necessary aspects for the hypothesis of tax incidence.